Hubungan Antara Pembelajaran Andragogi dan Keterampilan Belajar dengan Hasil Belajar Mahasiswa - Aldo Regeryo Evans Panganton; Yansen Alberth Reba; Mikhael Udam (Cenderawasih Journal of Counseling and Education, 2022)
This research aimed to determine the correlation between andragogy learning as well as learning skill and student learning outcome. The present research applied a quantitative research approach with multiple correlational analysis method where the data collection was carried out through questionnaire technique in the form of questionnaires and documentation. The research population involved students from the Guidance and Counseling Program, Faculty of Teacher Training and Education, Cenderawasih University batch 2018, 2019, 2020 and 2021 as many as 101 students. The determination of the sample was performed by total sampling technique in which the researcher used the entire sample with a total of 101 students. The research findings showed a correlation between andragogy learning and learning outcome with a Pearson correlation value of 0.502, a correlation between learning skill and learning outcome with a Pearson correlation value of 0.445 and a correlation between andragogy learning and learning skills and learning outcomes where the correlation coefficient was indicated by an R value of 0.573. Meanwhile, the simultaneous contribution of andragogy learning as well as learning skill and learning outcome was 32.8% (0.328) while the other 67.2% were determined by other variables not examined in this research. The conclusion of this research was that there was a fairly strong correlation between andragogy learning as well as learning skill and student learning outcome.